En defensa de una lectura autobiográfica del Retrato del artista en 1956 de Jaime Gil de Biedma - Iglesias Arellano, Mariana (El Colegio de México, 2025)
This paper defends an autobiographical reading of Jaime Gil de Biedma’s Retrato de un artista en 1956. I will attempt to demonstrate that the autofictional reading that has predominated since the publication of Javier Blasco’s study (1996) has led to important themes linked to homosexuality, prostitution and the sexual exploitation of minors being overlooked. It will be seen that the analysis of these themes, relegated by most critics to the extra-textual sphere, is central to an understanding of the author's literary proposal.